Effect of Graphene Oxide-Boron Nitride-Based Dual Fillers on Mechanical Behavior of Epoxy/Glass Fiber Composites. (9th August 2021) - Kavimani, V.; Gopal, P. M.; Stalin, B.; Karthick, Alagar; Arivukkarasan, S.; Bharani, Murugesan
Abstract : Graphene and its derivatives have excellent properties such as high surface area, thermal, and mechanical strength, and this fact made the researchers promote them as the possible filler material for fiber-matrix composite. The current research deals with validation on the effect of graphene oxide boron nitride filler over mechanical and thermal stability of epoxy glass fiber polymer matrix composite. The objective of this experimental investigation is to develop glass fiber reinforced polymer composites with hybrid filler addition. The matrix material selected is epoxy resin, whereas the glass fiber is selected as reinforcement, while boron nitride and graphene oxide are chosen as fillers. Compression moulding methodology is followed to develop the composites with the constant percentage of fiber loading, graphene oxide filler, and varying boron nitride content from 0 to 3 wt.% at an equal interval of 1 wt.%. The developed composite is analyzed for mechanical properties, and the fractured surface is analyzed through the scanning electron microscope. The addition of hybrid fillers enhances the fiber-matrix bonding strength and improves the thermal and mechanical properties up to a specific limit. Thermal gravimetric analysis was conducted to understand the thermal behavior of composite. The results revealed that the addition of filler improved the thermal stability of the composites.